The rationale, design, and methods of a randomized, controlled trial to evaluate the efficacy and safety of an active strategy for the diagnosis and treatment of acute pulmonary embolism during exacerbations of chronic obstructive pulmonary disease. Issue 3 (25th February 2019) - Jiménez, David; Agustí, Alvar; Monreal, Manuel; Otero, Remedios; Huisman, Menno V.; Lobo, José L.; Quezada, Andrés; Jara‐Palomares, Luis; Hernando, Ascensión; Tabernero, Eva; Marcos, Pedro; Ruiz‐Artacho, Pedro; et al.
Abstract : Introduction: Some previous studies have suggested a high prevalence of pulmonary embolism (PE) during exacerbations of chronic obstructive pulmonary disease (ECOPD). The SLICE trial aims to assess the efficacy and safety of an active strategy for the diagnosis and treatment of PE (vs usual care) in patients hospitalized because of ECOPD. Methods: SLICE is a phase III, prospective, international, multicenter, randomized, open‐label, and parallel‐group trial. A total of 746 patients hospitalized because of ECOPD will be randomized in a 1:1 fashion to receive either an active strategy for the diagnosis and anticoagulant treatment of PE or usual care (ie, standard care without any diagnostic test for diagnosing PE). The primary outcome is a composite of all‐cause death, non‐fatal (recurrent) venous thromboembolism (VTE), or readmission for ECOPD within 90 days after enrollment. Secondary outcomes are (a) death from any cause within 90 days after enrollment, (b) non‐fatal (recurrent) VTE within 90 days after enrollment, (c) readmission within 90 days after enrollment, and (d) length of hospital stay. Results: Enrollment started in September 2014 and is expected to proceed until 2020. Median age of the first 443 patients was 71 years (interquartile range, 64‐78), and 26% were female. Conclusions: This multicenter trial will determine the value of detecting PEs in patients with ECOPD. This has implications for COPD patient morbidity and mortality. Trial registration number: NCT02238639.